Legislative and judicial responses to public health protection under eco-environmental damage relief in China - Huaqi Li; Bei Liu (Frontiers Media S.A., 2023)
BackgroundThe group-type health damage caused by eco-environmental damage has been stated in the Environmental Protection Law and other laws in China. The first-ever Chinese Civil Code, which took effect in 2021, has explicitly defined eco-environmental damage relief and imposed affirmative duties on those who polluted the environment or destroyed the ecology. This study aims to describe the status quo of public health protection in eco-environmental damage relief and explore its progress and limits in protecting public health.MethodsBy reviewing China's legislation on relief of eco-environmental damage and observing the implementation of these laws in judicial practice. All judicial cases of eco-environmental damage published by Chinese courts from January 2021 to May 2023 were selected and examined. From the perspective of the comparison of laws, the measurement of interests and the execution of cases, we discussed the issues of China's legislative and judicial responses to public health.ResultsThe relief system of eco-environmental damage in China has been formed initially, but there are still some deficiencies: In the application of law for relief of public health, there are many choices of means, resulting in the choice conflict of law application; the public health damage in the eco-environmental damage case has been ignored by courts, and it has not been a dominant consideration element; the objects of the execution of the cases are directed to the pure eco-environmental restoration, and the restoration plan does not cover public health protection measures, which does not have a preventive effect on public health. The root cause of problems is that the relief of eco-environmental damage in China follows the logic of traditional private law.ConclusionThe issues mentioned above merit consideration in China's future law revisions and judicial practice. Based on the dual nature of public and private law in environmental health, it is necessary to adjust the provisions of responsibility for eco-environmental restoration from the framework of public law, including the scope and mechanism, and then further suggestion includes the legal subject, the benefit element and the use of funds.